Acanthocopinae (Crustacea: Isopoda: Munnopsididae) from the Southern Ocean deep sea with the description of Acanthocope eleganta sp. nov. - Malyutina, Marina; Brandt, Angelika (Zootaxa, 2004)
Acanthocope eleganta sp. nov. is described from the abyssal Southern Ocean near the Southern Ocean Peninsula. The new species differs from others in the following: a slender dorsomedial spine on the pleon anteriorly, a pair of short dorsal spines and long ventral spine on each of pereonites 5 and 6; uropods half as long as the terminal spine of the pleotelson and with a minute exopod. A. annulatus Menzies, 1962 is redescribed; A. galatheae Wolff, 1962, previously known only from the Gulf of Panama and from Angola Basin, is recorded from the northwest Weddell Sea.